2021
DOI: 10.1088/1361-6668/abe4b6
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic properties of curved HTS trapped field stacks under high-frequency cross fields for high-speed rotating machines

Abstract: Superconducting electric propulsion systems, characterized by high power densities and efficiencies, provide a possibility to zero carbon emission for future aviation. Stacks of high temperature superconductor (HTS) coated conductors (CCs) have become an alternative for high field magnets applied to superconducting machines, given their excellent field trapping ability and thermal stability. High-frequency ripple fields always exist in high-speed electric machines. Most research work regarding HTS trapped fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…In [110], an A-V formulation-based numerical model has been extended from 2D to 3D for simulating the magnetization of superconductors. The electromagnetic characteristics of curved HTS TFSs exposed to high-frequency cross fields have been explored in [111] through the H-formulation-based numerical modelling. It is concluded that the 2D axisymmetric model to approximate a square TFS as a round bulk is inapplicable for studying the electromagnetic distributions of TFSs; thus, a 3D model has to be employed [111].…”
Section: Modelling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [110], an A-V formulation-based numerical model has been extended from 2D to 3D for simulating the magnetization of superconductors. The electromagnetic characteristics of curved HTS TFSs exposed to high-frequency cross fields have been explored in [111] through the H-formulation-based numerical modelling. It is concluded that the 2D axisymmetric model to approximate a square TFS as a round bulk is inapplicable for studying the electromagnetic distributions of TFSs; thus, a 3D model has to be employed [111].…”
Section: Modelling Methodsmentioning
confidence: 99%
“…The electromagnetic characteristics of curved HTS TFSs exposed to high-frequency cross fields have been explored in [111] through the H-formulation-based numerical modelling. It is concluded that the 2D axisymmetric model to approximate a square TFS as a round bulk is inapplicable for studying the electromagnetic distributions of TFSs; thus, a 3D model has to be employed [111]. An H-formulation-based full 3D time-dependent numerical model for Roebel cables has been proposed in [112].…”
Section: Modelling Methodsmentioning
confidence: 99%
“…Additionally, a typical commercial HTS tape is composed of not only the HTS layer but also the non-superconducting overlayer, substrate as well as stabilisers. Therefore, the electromagnetic interactions between the HTS and non-superconducting layers cannot be considered in the analytical equations, especially at high frequencies [33,34]. In addition, the analytical formulae are limited to simple structures, e.g.…”
Section: Numerical Modelling Of Dynamic Resistancementioning
confidence: 99%
“…As the operating mode (rating) is changed the motor shaft speed also changes. Magnetic losses in the magnetic circuit of the traction motor depend on the motor shaft speed [191][192][193].…”
Section: Model Of Pulsating Current Traction Motor Taking Into Consideration Magnetic Losses In Steelmentioning
confidence: 99%